Promoting English Vocabulary for Autistic Students by Using Speech Therapy (An Action Research in Sunan Muria Extraordinary School, Kudus) - Farid Noor Romadlon (Vision: Journal for Language and Foreign Language Learning, 2017)
The opportunity to learn English should be given to all learners since English has been widely spread globally. Learners should be exposed to English as early as possible and be prevalent for all, including disabled students. Students who need special treatment in learning should also get equal opportunity to study, especially English. One type of disabled students who need special attention in English learning is those who have autism. Autistic students are in need of special treatment learning English since they have more difficulties in perceiving and producing language code. Therefore, English teachers should have awareness of the characteristics of autistic students concerning speech difficulties. It is highly necessary for autistic students to have intensive therapy and in other sides, they also have a right to learn foreign languages like English. Speech therapy as one of the therapies used to assist the autistic students in producing language codes is potentially in line with English learning. In this case, speech therapy can be done while teaching English to autistic students because speech therapy often requires graded language teaching.    This study focuses on how speech therapy is integrated with English teaching for autistic students in Second Grader of Junior High School students to improve their English proficiency and speech competence as well. The study is an ongoing classroom action research conducted in SMP Sunan Muria in Kudus Regence, Central Java, Indonesia.